Frederick W. Lowndes, MRCSE and Surgeon to the Liverpool Lock Hospital: Prostitution and Venereal Disease in the 1880s - María Isabel Romero Ruiz (Miscelánea: A Journal of English and American Studies, 2016)
The aim of this paper is to analyse the perpetuation of the myth of the fallen woman in the rescue work and the cure of prostitutes in Liverpool in the 1880s. To this end, Frederick Lowndes’ 1886 publication, Prostitution and Venereal Diseases in Liverpool, will be discussed as an example of a text written by a medical authority concerned with sexual promiscuity and the spread of venereal disease. Prostitution had cultural and moral implications for Victorians, and prostitutes represented a threat to middle-class society as the very image of vice and public disorder itself. Lowndes offers an overview of the issue for the years leading up to the publication of his pamphlet, dealing with issues like the role of brothels, the causes of prostitution in Liverpool and the classification of these women into different categories, thus echoing some of the ideas of moral reformers and medical men concerning the Great Social Evil. The role played by local laws in the containment of this public vice and of the Liverpool Lock Hospital in the treatment of the diseases considered to be the result of prostitution will be analysed in the light of Lowndes’ text and ideas. My intention is to prove that seclusion of deviant elements of society together with their classification and indoctrination were still present in the medical and moral discourses of the latter part of the Victorian period. Similarly, Foucauldian notions concerning deviancy and discipline will be discussed together with Butlerian ideas about gender and sexuality in the context of Victorian respectability and womanhood.